Yield Trial of Sixteen Tall and Dwarf Wheat Varieties (Triticum aestivum L.) Grown in the Libyan Desert - EL-SHARKAWY, M. A.; SGAIER, K. (The Libyan Journal of Agriculture, 2023)
The grain yield and grain size of 16 varieties of common wheat (Triticum aestivum L) were compared under the desert conditions of Al-Kufra oasis in the southern region of the Libyan Arab Republic. Sidi-Misri 1, a local selection from the dwarf Mexican wheat, was found to be the highest yielding variety (5.240 tons/ha). On the other hand the commonly used variety. Florence Aurora, was significantly lower in grain yield (3.464 tons/ha). The grain size, as estimated by the weight of 1,000 grains, for Sidi Misri 1, Florence Aurora and many other varieties were greatly reduced when grown under the conditions of Al-Kufra oasis.